Evaluasi Sistem Informasi Manajemen Hotel Dengan Metode Unified Theory Of Acceptance And Use Of Technology (UTAUT) 2 Di Bina Darma Hotel Palembang - Yosef Estrada; Muhammad Sobri (LPPM UBHINUS MALANG, 2022)
At Bina Darma Hotel Palembang already using a management information system to assist in managing and serving customers who will stay, with the information system the Bina Darma especially staff or employees who work can work efficiently. However, the implementation of this information system has not been evaluated during the use of the system, this makes it unknown whether this management information system has been fully accepted by system users. application of the UTAUT 2 model in knowing and understanding the use of system performance. UTAUT 2 is a new technology acceptance model developed by Venkatesh et al. In this study there are variables measuring Behavioral Intention and use behavior. So it is necessary to evaluate the information system to measure the extent to which this information system can be accepted by users, especially employees and staff within the scope of Bina Darma Hotel. In order to support evaluating the use of the Bina Darma Hotel management information system, it is necessary to support a method, a method that can evaluate system acceptance. This method is the Unified Theory of Acceptance and Use of Technology (UTAUT) 2. So based on these problems it is necessary to conduct an evaluation of the existing management information system at Bina Darma Hotel.